Radiation-Induced Reprogramming of Pre-Senescent Mammary Epithelial Cells Enriches Putative CD44+/CD24−/low Stem Cell Phenotype - Gao, Xuefeng; Sishc, Brock J.; Nelson, Christopher B.; Hahnfeldt, Philip; Bailey, Susan M.; Hlatky, Lynn (Frontiers in Oncology, 2016)
The enrichment of putative CD44+/CD24-/low breast stem cell populations following exposure to ionizing radiation has been ascribed to their inherent radioresistance and an elevated frequency of symmetric division during repopulation. However, recent studies demonstrating radiation induced phenotypic reprogramming (the transition of non CD44+/CD24-/low cells into the CD44+/CD24-/low phenotype) as a potential mechanism of CD44+/CD24-/low cell enrichment have raised the question of whether a higher survival and increased self-renewal of existing CD44+/CD24-/low cells or induced reprogramming is an additional mode of enrichment. To investigate this question, we combined a cellular automata model with in vitro experimental data using both MCF-10A non-tumorigenic human mammary epithelial cells and MCF-7 breast cancer cells, with the goal of identifying the mechanistic basis of enriching the CD44+/CD24-/low cell pool in the context of radiation-induced cell senescence. Quantitative modeling revealed that incomplete phenotypic reprogramming of pre-senescent non-stem cells (reprogramming whereby the CD44+/CD24-/low phenotype is conveyed, but along with the short-term remaining proliferation capacity of the original cell) could be an additional mode of enriching the CD44+/CD24-/low subpopulation. Further, the stem cell enrichment in MCF-7 cells occurs both at lower doses and earlier time points, and has longer persistence, than that observed in MCF-10A cells, suggesting phenotypic plasticity appears to be less regulated in breast cancer cells. Taken together, these results suggest that reprogramming of pre-senescent non-stem cells may play a significant role in both cancer and non-tumorigenic mammary epithelial populations following exposure to ionizing radiation, a finding with important implications in radiation therapy and radiation carcinogenesis.